2000
DOI: 10.1080/00039890009603379
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diesel Exhaust on Neurobehavioral and Pulmonary Functions

Abstract: Ten railroad workers and 6 electricians referred for shortness of breath also had slowness of response, memory loss, and disordered sleep, all of which suggested neurobehavioral impairment. The hypothesis was that diesel exhaust causes central nervous system impairment. Six electricians worked within enclosed concrete walls and roofs that trapped diesel exhaust from trucks. Seven railroad mechanics had tuned diesel engines indoors for 15-50 y, and 3 crewmen rode in locomotives. Neurobehavioral and visual funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…[1] Ever since, studies of the relationship between air pollution and cognitive function have been a point of focus. Residential proximity to a major roadway is a commonly accepted method for determining long-term air pollution exposure.…”
Section: Air Pollution and Cognitive Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Ever since, studies of the relationship between air pollution and cognitive function have been a point of focus. Residential proximity to a major roadway is a commonly accepted method for determining long-term air pollution exposure.…”
Section: Air Pollution and Cognitive Dysfunctionmentioning
confidence: 99%
“…However, impact on the central nervous system (CNS) was first described only a decade ago. [1] A significant number of clinical and epidemiological studies indicate adverse associations between air pollution and neurological disease, but mechanistic pathways remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 13 shows two 3 PAHs, one light, and two heavy versus particles size for summer, 2005. The presence of PAHs in the ultrafine size mode shows a finer aerosol size that may have health consequences (Kilburn et al 2000;Parent et al 2007) as indicated by data on PAHs from diesel trucks (Zielinska et al 2004). …”
Section: Analysis Of Organic Componentsmentioning
confidence: 99%
“…One of these studies found a potential adverse effect of air pollutants in Mexico City on the CNS of dogs (Calderón-Garcidueñas et al, 2002). In humans, a subsequent study showed neurobehavioral and pulmonary impairment in railroad workers and electricians (Kilburn, 2000). Furthermore, X-ray fluorescence analysis in a kinetics report revealed that metal elements of DEP, which contained nano-sized particles, were detected in the olfactory epithelium and bulb of mice (Matsui et al, 2009).…”
mentioning
confidence: 99%